2010
DOI: 10.1590/s1980-65232010000400017
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic treatment of a 36-mm long upper cuspid: clinical case report

Abstract: Purpose: To report a clinical case of a 36 mm long upper cuspid submitted to root canal treatment, with emphasis on the alternative technique employed.Case description: A 32 years old, male patient had suffered subluxation of teeth 12 and 13 and coronal fracture involving enamel and dentin, as well as pulp exposition, of tooth 14 because of a motorcycle accident. The man was given dental assistance and a semi-rigid splinting of teeth numbers 12 and 13 was carried out followed by the root canal treatment in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Few studies about root canal treatment of long teeth are reported in the literature, ranging from 32 to 42 mm of WL (Al-Dahman et al, 2017;Barletta et al, 2010;Bellizzi, 1982;Booth, 1988;Cardoso et al, 2019;Hussain & Awooda, 2020;Maden et al, 2010;Vargo & Hartwell, 1992;Venokur & Fink, 1976;Zmener, 2003). However, some authors revealed the existence of extremely long teeth, with maxillary canines ranging from 41 to 52 mm (Booth, 1988;Hayward, 1980;Marashi & Gorlin, 1990;Wilkie & Chambers, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Few studies about root canal treatment of long teeth are reported in the literature, ranging from 32 to 42 mm of WL (Al-Dahman et al, 2017;Barletta et al, 2010;Bellizzi, 1982;Booth, 1988;Cardoso et al, 2019;Hussain & Awooda, 2020;Maden et al, 2010;Vargo & Hartwell, 1992;Venokur & Fink, 1976;Zmener, 2003). However, some authors revealed the existence of extremely long teeth, with maxillary canines ranging from 41 to 52 mm (Booth, 1988;Hayward, 1980;Marashi & Gorlin, 1990;Wilkie & Chambers, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the strategies of treating long teeth, four strategies were found in order to compensate the limitations of the endodontic instruments: endodontic instrument adaptation (Bellizzi, 1982;Cardoso et al, 2019;Hussain & Awooda, 2020), changing the reference edge of the endodontic instrument (Al-Dahman et al, 2017;Barletta et al, 2010;Vargo & Hartwell, 1992), wearing the crown by drill in order to reach the ideal WL, and using veterinary files.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations